One‐Step Preparation of All‐Natural Pickering Double Emulsions Stabilized by Oppositely Charged Biopolymer Particles. Issue 23 (10th November 2021) - Li, Yunxing; Gong, Suijing; Guan, Xin; Jiang, Hang; Tao, Shengnan; Yang, Cheng; Ngai, To
Abstract: Double emulsions are complex fluid systems, which offer significant advantages over simple single emulsions for encapsulation, protection, and sustained release of cargos. However, they are thermodynamically unstable systems. Double emulsions are usually prepared using two sets of surfactants with different hydrophilic–lipophilic balance values. However, these surfactants often interfere with each other, thus affecting the emulsion stability. Colloidal particles have also been used to prepare double emulsions, which are known as Pickering double emulsions. The formulated double system is, however, temporary, and the adjustment of particle wettability is cumbersome and expensive. Here, the authors report a one‐step emulsification process to generate water‐in‐oil‐in‐water double emulsions using two oppositely charged, plant‐derived particles, zein nanoparticles, and cellulose nanocrystals as stabilizers. The stabilization is attributed to the adsorption of aggregates formed by the two types of particles through electrostatic attraction at the oil–water interface with different curvatures. The application of co‐encapsulation of β‐carotene and epigallocatechin gallate is demonstrated, which synergistically improves their stability under different conditions. Therefore, the formulated all‐natural Pickering double emulsions can find applications in various industries, including food, pharmaceutics, and cosmetics. Abstract : A novel approach to prepare all‐natural Pickering double emulsions by a one‐step emulsification process is described. It is demonstrated that the stabilization mechanism of the double emulsion is attributed to the amphiphilicity of aggregates consisting of oppositely charged, bio‐based particles and phase inversion process of the emulsion. Additionally, the encapsulation and protection of both polar and apolar cargos are achieved.